1994
DOI: 10.1104/pp.105.4.1433
|View full text |Cite
|
Sign up to set email alerts
|

Light-Stimulated Cotyledon Expansion in the blu3 and hy4 Mutants of Arabidopsis thaliana

Abstract: Cotyledon expansion in response to blue light was compared for wild-type Arabidopsis thaliana (1.) Heynh. and the mutants blu3 and hy4, which show reduced inhibition of hypocotyl growth in blue light. White, blue, and red light stimulated cotyledon expansion in both intact and excised cotyledons of wild-type seedlings (ecotypes No-O, WS, Co-O, La-er). Cotyledons on intact blu3 and hy4 seedlings did not grow as well as those on the wild type in response to blue light, but pretreatment of blu3 seedlings with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…For stimulation of cotyledon expansion by red light, both phytochrome A and B are required while, under far-red light, only phytochrome A is responsible (Reed et al, 1994). The cotyledon expansion elicited by phytochrome B is cell autonomous , while that induced by blue light is only observed in intact plants (Blum et al, 1994). We observed that cotyledon expansion induced by continuous white light was not blocked by DCMU (data not shown).…”
Section: Discussionmentioning
confidence: 66%
“…For stimulation of cotyledon expansion by red light, both phytochrome A and B are required while, under far-red light, only phytochrome A is responsible (Reed et al, 1994). The cotyledon expansion elicited by phytochrome B is cell autonomous , while that induced by blue light is only observed in intact plants (Blum et al, 1994). We observed that cotyledon expansion induced by continuous white light was not blocked by DCMU (data not shown).…”
Section: Discussionmentioning
confidence: 66%
“…In addition to its role in activating stomatal opening and chloroplast movement, blue light activates at least two other responses in leaves: leaf expansion Blum et al, 1994;Van Volkenburgh, 1999) and, in certain species, solar tracking (Voerkel, 1934;Yin, 1938). Therefore, it was of interest to determine the distribution of phot1 in leaves.…”
Section: Localization Of Phot1-gfp In Mature Leavesmentioning
confidence: 99%
“…Next are bending responses, operating within the time scale of hours. The slowest are reactions of cotyledon expansion, which take days (2). However, it is quite possible that all these reactions may be induced simultaneously (moreover, they could be linked), and the observed difference originates merely from different rates and delays in metabolic or long-distance-transport processes that mediate BL responses at the whole-plant level.…”
mentioning
confidence: 99%
“…Among numerous physiological processes controlled by BL are phototropism (bending toward or away from the light source), cotyledon expansion, and inhibition of hypocotyl elongation (1)(2)(3). These reactions are preceded or accompanied by significant changes in electrochemical properties of cells and tissues, including changes in membrane potential and ion transport across membranes (4)(5)(6).…”
mentioning
confidence: 99%